Unrecorded Marriage Heart Rights According To Positive Law And Islamic Law - Muhammad Yusuf Siregar; Nurhayati; DhiauddinTanjung (CV. AFDIFAL MAJU BERKAH, 2022)
The problem in this research is related to the importance of marriage registration. In addition to its substance to realize legal order, it also has preventive benefits for both parties. Marriages that are not recorded will have a negative impact (loss) on the wife, children, and/or husband. By law, as the wife of a marriage that is not recorded, it is considered an illegitimate husband and wife. The wife is not entitled to a living, inheritance and other assets in the event of separation or death because the marriage is considered to have never occurred. The formulation of the research problem is First, how is the impact of unregistered marriage laws for children according to positive law and Islamic law, second, how are the legal solutions offered for marriages that are not registered according to positive law and Islamic law. The research method used is normative juridical and comparative law to analyze legal problems that refer to legal norms contained in legislation and court decisions as well as solutions offered in dealing with these problems.